Assessing flood vulnerability on livelihood of the local community: A case from southern Bagmati corridor of Nepal. (December 2021) - Shreevastav, Bitu Babu; Tiwari, Krishna Raj; Mandal, Ram Asheshwar; Nepal, Abhishesh
Abstract: Flood is one of the prominent hazards in the Terai region of Nepal. This study was objectively conducted to assess the livelihood vulnerability of community living in the up-stream, mid-stream and down-stream regions at southern Bagmati River corridor, Nepal. To meet the objective, primary data were collected through house hold survey using random sampling technique with 25% (182 HHs) sample size, focus group discussion (6) and key informant interview (15) carried out in Rautahat and Sarlahi districts of Nepal to accomplish this task. A pre-tested semi-questionnaire and check list was prepared based on the method of LVI given. LVI- IPCC was also used to collect required information. The results showed that the highest indexed value of socio-economic component was 0.360 of community living in the down-stream region and the least value was 0.157 of local people living in the up-stream region. Similarly, the indexed value of livelihood component was the highest (about 0.493) of the community living in the mid-stream belt. The indexed value of social network component was the highest (about 0.590) of the community living at mid-stream belt. But the indexed value of financial component was the highest (0.686) in the down-stream region. The indexed value of physical component was the highest (1) of the community living in the mid-stream region. The highest indexed value (0.464) was found of community living in the down-stream area. The indexed value of water resource component was the highest (0.366) of community living in the down-stream area. Similarly, the indexed value of natural hazard and climate variability component was the highest (0.579) of community living in the down-stream region. The livelihood vulnerability index values were the highest (0.528) of the community living in the down-stream belt. This indicates that the community living in the down-stream area was the most vulnerable to flood, but the community living in the up-stream belt the least vulnerable (0.323). The value of exposure was the highest (about 0.579) of community living in the down-stream belt while this was the lowest (about 0.291) of the community living in the up-stream belt. The sensitivity value was the highest (around 0.465) of the community living in the down-stream belt. The adaptive capacity was the highest (around 0.496) of the community living in the down-stream region. This also indicates that communities living in the down-stream area are most vulnerable to the flood. This study helps the scientific community to understand the differential effect of flood on up-stream and down-stream communities Highlights: Livelihood Vulnerability Index by Haln et al. (2009) & LVI-IPCC used to measure flood vulnerability Results showed higher flood vulnerability in downstream region (highest LVI value 0.528), Medium flood vulnerability in mid-stream (LVI value 0.506) & least in up-stream (LVI value 0.323); Highest indexed value of socio-economic component (0.360) of community living in the down-stream; Community in down stream are having more livelihood vulnerable to floods in compare to mid & up steam LVI can be a vital tool to analyze vulnerability and implement livelihood activities.